The Influence of the Tourism Sector on Regional Financial Performance (Department of Culture and Tourism of Majene Regency) - Aswar Rahmat (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2022)
The purpose of this study was to determine the effect of the tourism sector on regional financial performance. In the data analysis technique using simple linear analysis, the sample of this research is the data on the realization of consistent financial reports from 2018 to 2020 as many as 36 samples. The data sources used are primary data obtained by interviewing and secondary data obtained from related documents such as financial reports and organizational structures. the location of this research is located at Jln. Gen. Ahmad Yani No. 108 sub-districts of Banggae, Majene Regency. The research results obtained are the influence of the Tourism Sector which has a significant effect on Financial Performance area . Calculated using SPSS obtained from the analysis of the t test with the value of T Count of 3,631 greater than t table 2,032 with a significance value of 0.000 <0.05. The regression coefficient value is 0.05 which has a positive direction indicating that the better tourism is managed, the more optimal regional financial performance will be